2017
DOI: 10.1681/asn.2016111215
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a Mediates Endothelial Dysfunction in CKD

Abstract: CKD is an independent risk factor for cardiovascular disease (CVD). The accumulation of uremic toxins in CKD induces oxidative stress and endothelial dysfunction. MicroRNA-92a (miR-92a) is induced by oxidative stress in endothelial cells (ECs) and involved in angiogenesis and atherosclerosis. We investigated a role for oxidative stress-responsive miR-92a in CKD. Our study of patients at three clinical sites showed increased serum miR-92a level with decreased kidney function. In cultured ECs, human CKD serum or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 35 publications
3
79
0
3
Order By: Relevance
“…This later finding is in contrast to our results, since a slight increase in GSH in uremic endothelial cells has been observed, which could be a compensatory response against the prooxidant state present in endothelial cells in response to the uremic milieu. However, and in agreement with the previous and another study, uremic endothelial dysfunction was improved by NAC [28,35], as well as by ebselen. Furthermore, the combined effect of ebselen and NAC on GSH levels were additive in uremic endothelial cells, suggesting a beneficial effect of enhancing the GPx pathway in CKD-induced ED.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This later finding is in contrast to our results, since a slight increase in GSH in uremic endothelial cells has been observed, which could be a compensatory response against the prooxidant state present in endothelial cells in response to the uremic milieu. However, and in agreement with the previous and another study, uremic endothelial dysfunction was improved by NAC [28,35], as well as by ebselen. Furthermore, the combined effect of ebselen and NAC on GSH levels were additive in uremic endothelial cells, suggesting a beneficial effect of enhancing the GPx pathway in CKD-induced ED.…”
Section: Discussionsupporting
confidence: 93%
“…A recent systematic review [25] of clinical trials, assessing the effects of antioxidant therapy in CKD patients, indicates that N-acetylcysteine (NAC) has promising effects by decreasing the levels of oxidative stress markers and in a small study it reduced the risk of cardiovascular events in dialysis patients [26]. Furthermore, NAC improves endothelial dysfunction in dialysis patients [27] and in an in vitro model of uremic dysfunction [28].…”
Section: Introductionmentioning
confidence: 99%
“…Uremic toxins may induce various pathophysiological effects promoting the release or inhibition of different miRs. Recently, Shang et al [29] demonstrated that increased levels of miR-92a in serum correlated with impaired kidney function. The authors have shown that treatment of endothelial cells (EC) with uremic serum or uremic toxins (such as IS) led to up-regulation of miR-92a with a parallel reduction of miR-92a targets [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Shang et al [29] demonstrated that increased levels of miR-92a in serum correlated with impaired kidney function. The authors have shown that treatment of endothelial cells (EC) with uremic serum or uremic toxins (such as IS) led to up-regulation of miR-92a with a parallel reduction of miR-92a targets [29]. Such a decreased expression of key protective molecules resulting in impaired function of EC may predispose to the development of progressive atherosclerosis and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Indole is then absorbed via gut villi and enters the portal system of liver, where it is sulphated and metabolized into IS. Indoxyl sulphate is a protein‐bound small molecule uremic toxin and is harmful for various cells, particularly vascular endothelial cells . In CKD patients, the excretion of IS is impaired, and it is thus accumulated in the body and leads to a vicious cycle .…”
Section: Indoxyl Sulphate a Uremic Toxin Originated From Human Gutmentioning
confidence: 99%